2005
DOI: 10.1104/pp.105.067561
|View full text |Cite
|
Sign up to set email alerts
|

Differential Capacity for High-Affinity Manganese Uptake Contributes to Differences between Barley Genotypes in Tolerance to Low Manganese Availability

Abstract: There is considerable variability among barley (Hordeum vulgare) genotypes in their ability to grow in soils containing a low level of plant available manganese (Mn). The physiological basis for the tolerance to low Mn availability is unknown. In this work, Mn 21 influx and compartmentation in roots of the Mn-efficient genotype Vanessa and the Mn-inefficient genotype Antonia were investigated. Two separate Mn transport systems, mediating high-affinity Mn 21 influx at concentrations up to 130 nM and lowaffinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 34 publications
1
61
1
Order By: Relevance
“…The finding that only 10% of the Mn is associated with wild-type vacuoles is surprising in view of other studies indicating that most Mn is stored in the vacuole. Based on Mn broadening of 31 P NMR signal or on the analysis of 54 Mn radiotracer release kinetics, two groups concluded that most Mn is stored in the vacuoles of maize (Zea mays) and barley root cells, respectively (Quiquampoix et al, 1993;Pedas et al, 2005). The discrepancy with our results may be explained by the use of different experimental approaches, by a different intracellular distribution of Mn in root and mesophyll cells, or by differences in Mn storage between species.…”
Section: Atnramp3 and Atnramp4 Operate In The Retrieval Of Mn From Vacontrasting
confidence: 55%
“…The finding that only 10% of the Mn is associated with wild-type vacuoles is surprising in view of other studies indicating that most Mn is stored in the vacuole. Based on Mn broadening of 31 P NMR signal or on the analysis of 54 Mn radiotracer release kinetics, two groups concluded that most Mn is stored in the vacuoles of maize (Zea mays) and barley root cells, respectively (Quiquampoix et al, 1993;Pedas et al, 2005). The discrepancy with our results may be explained by the use of different experimental approaches, by a different intracellular distribution of Mn in root and mesophyll cells, or by differences in Mn storage between species.…”
Section: Atnramp3 and Atnramp4 Operate In The Retrieval Of Mn From Vacontrasting
confidence: 55%
“…In plants, similar results were absent until recently because of the difficulty in monitoring Mn uptake in realistically low concentrations of Mn. Recently, the existence of two separate Mn transport systems mediating high-affinity and low-affinity uptake of Mn 2+ was elegantly shown in winter barley (Hordeum vulgare; Pedas et al, 2005). The iron-regulated transporter IRT1 represents a putative pathway for entry of Mn into the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is usually cultivated under anaerobic conditions, where Mn concentration in soil solution is very high due to soil reduction (Sasaki et al, 2011), while barley is an upland plant, which is cultivated in low Mn conditions (Pedas et al, 2005). Although both OsNramp5 in rice and HvNramp5 in barley mediate Mn uptake by the roots (Sasaki et al, 2012, Fig.…”
Section: Different Uptake System For Mn and CD Between Rice And Barleymentioning
confidence: 99%